A Román állam területi kialakulásának története I. : középkortól a román királyság kikiálltásáig (1881) - Csüllög, Gábor; Gulyás, László (Közép-Európai Közlemények, 2012)
European states are of various ages. The formation of the statehood of some of them took place in the Middle-Ages, and they have existed in dynastic relations, though in different ways, ever since. Others are young states which have become independent statehoods in the 19th and 20th centuries, either by breaking away from earlier states or by transforming their dependent and partial statehood in opposition to power politics. Such areas in Europe are the Balkan and Eastern-Europe, among whose young states Romania stands out because of the special historical development of its statehood and its territorial changes. The Romanian state became an independent European state over several historical periods, by building from several territorial bases, and through various kinds of political dependence, at the end of the 19th century. Later on, it grew its territory several times as a result of its peculiar 20th century politics. Until the end of the 19th century, it had consisted of two similarly structured but separate principalities: Wallachia and Moldova. The historical periods of the Romanian statehood basically correspond to the political processes dictated by the power states of the Balkan, Eastern- and Central-Europe, as its territory had shaped in their buffer zone.